ALAT TRANSPORTASI KASULTANAN NGAYOGYAKARTA HADININGRAT DALAM PERSPEKTIF INTEGRASI STRUKTURAL - Indro Baskoro Miko Putro (Institut Seni Indonesia Yogyakarta, 2013)
The means of transport belonging to the palace of Yogyakarta Sultanate is treated asan heirloom that gets legitimacy sultan as Kagungan Dalem (the king) in accordance habitswithin the palace. Royal heirlooms, including transportation and the name has a certain degreeof corresponding 'proximity' to the sultan. Heirloom that has been used or is still used by theSultan and was named Kyai masculine , while the feminine was named Nyai. If the vehicle is amajor heirloom, then in front of Kyai or Nyai title is added to the title Kanjeng.Palace as the creator of